Clinical signs in the Wernicke-Korsakoff complex: a retrospective analysis of 131 cases diagnosed at necropsy. Issue 4 (April 1986) - Harper, C G; Giles, M; Finlay-Jones, R
Abstract : A recent necropsy study has shown that 80% of patients with the Wernicke-Korsakoff syndrome were not diagnosed as such during life. Review of the clinical signs of these cases revealed that only 16% had the classical clinical triad and 19% had no documented clinical signs. The incidence of clinical signs in this and other retrospective pathological studies is very different from that of prospective clinical studies. This discrepancy may relate to "missed" clinical signs but the magnitude of the difference suggests that at least some cases of the Wernicke-Korsakoff syndrome may be the end result of repeated subclinical episodes of vitamin B1 deficiency. In order to make the diagnosis, clinicians must maintain a high index of suspicion in the "at risk" group of patients, particularly alcoholics. Investigations of thiamine status may be helpful and if the diagnosis is suspected, parenteral thiamine should be given.